Paleogeodynamical characteristics of central part of the Transcarpathian Seismic Zone’ rocks with combined geophysical and mineralogical investigations - TOLSTOI, M.; KADURIN, V.; SHABATURA, O.; KOSTENKO, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Shortly in this article is described the results of the investigations of paleogyodynamical characteristics of indicative site of central part of the Transcarpathian Seismic Zone with using structural-geodynamical mapping method as well radium survey and mineralogical testing.